Działania Parlamentu Europejskiego na rzecz ochrony praw konsumenta w Unii Europejskiej - Łokuciejewska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Activities of the European Parliament aimed at the protection of a Union citizen who through their everyday purchasing decisions becomes a consumer. Consumer rights wchich are covered by the largest protection in the Union are: rights to safeness, health and to accurate information. The protection of these rights leads to the implementation of the right to protection of economic interests. This is reflected in the regulation of advertising, when concluding a contract, or food production. Through the realization of these objectives, the economic interests of consumers are already protected itself. The citizen in the European Union through the activities of Parliament and the Council, feels safe and likes to make purchases and is able to maximize his satisfaction thus, Council with the Parliament discuss on the directives that actually respond to problems reported by consumers.
Keywords: Parlament Europejski; Unia Europejska; prawa konsumentów